Wpływ wilgotności i gatunku gleby na wzrost mikoryzowanych sadzonek sosny zwyczajnej (Pinus sylvestris L.) - Buraczyk, Włodzimierz; Aleksandrowicz-Trzcińska, Marta; Drozdowski, Stanisław; Szeligowski, Henryk (Leśne Prace Badawcze, 2012)
The paper presents results of research on the growth of 1-year old Scots pine seedlings inoculated with the mycorrhizal fungus Hebeloma crustuliniforme , grown on substrates of differing moisture content; 40%; 55% and 70%. The experiment was carried out under controlled conditions on seedlings growing under a foil tent, in loose sand and saw dust. After five months, the aboveground growth of the seedlings was measured and root growth was analyzed using the software WinRhizo 2002c. The chemical and physical properties of the substrate had no significant effect on the growth of the seedlings. The root collar diameter, needle length and dry mass were larger in the more fertile growing medium, containing more saw dust, than in the sandy one, but there was no clear effect of humidity on these traits. The use of different substrates had the greatest impact on the development of the root systems. In sand with increasing humidity, from 40%, through 55% to 70%, the seedlings produced larger root systems, whereas in the saw dust substrate the highest humidity (70%) significantly reduced growth.